Customer Data Management Information System And Web-Based Digital Product Sales In CV. IT Brain Indonesia - Muhammad Syafri Romadhon; Yulian Findawati (Universitas Muhammadiyah Sidoarjo, 2021)
Customer Data Management Information System is a program or information system that functions to assist customer and sales data recording activities as well as product activation processes on CV. IT Brain Indonesia. This system is designed to record and input customer data from requests for demo software and customer consultations that come in daily via email marketing and also through whatsapp marketing before making a purchase and activation process. This system is shown for the marketing team on CV. IT Brain Indonesia is still using Microsoft Excel to record these data, which takes a long time to group customer needs on different sheets. In this case the author designed an Information System for Customer Data Management and Web-Based Digital Product Sales at CV. IT Brain Indonesia. The method used is the equivalence method and blackbox testing. The results of this study are in the form of a web-based information system intended for marketing and customer support that can group customer data according to their needs and record sales and product activation processes. This web-based information system was created using the CodeIgniter framework.